High school students’ perceptions of alcohol prevention programs - Ogenchuk, Marcella (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
The purpose of this study was to explore Grade 11 students’ perceptions of programs related to the prevention of alcohol use in high school settings through an analysis of quantitative and qualitative data elicited from student questionnaires (n=452) and focus groups. It was found that students felt a need for increased information on alcohol education at the high school level. They identified content and preferred methods of delivery to improve cognitive, behavioral, and emotional engagement. Several metapolicy implications arose. At a broader policy level, provincial ministries may consider systematic collection of data to monitor youth alcohol use, as well as to inform educational programs and evaluate their efficacy. Keywords: Prevention of alcohol use in youth, students’ perceptions, high school alcohol prevention programs, alcohol education